TEACHING WRITING HORTATORY EXPOSITION TEXTS THROUGH GENRE-BASED APPROACH AT SMA NEGERI 2 PINRANG - Irma Yuliana Saputri (La Parole : Journal of Language Teaching and Pedagogy, 2021)
Writing is considered a difficult skill for students. Regarding the reality, the Indonesian government has put one approach in curricula namely genre-based approach that makes the researcher interested to formulates two research objectives in this research. They are to find out the extent to which the using genre-based approach helps teachers in teaching writing hortatory exposition texts and to know the students’ interest in the implementation of the genre-based approach in learning writing hortatory exposition texts at SMA Negeri 2 Pinrang. The researcher applied the triangulation mix method and used purposive sampling. To obtain the data, the researcher used three instruments, namely observation, interview, and questionnaire. After analyzing the data, the research result indicated a genre-based approach helpful to teachers in teaching writing hortatory texts. Further, the students’ interests categorize as strongly interest. Keywords: Genre-based Approach, Writing, Hortatory Exposition Texts.